A Syrian refugee with meningococcal empyema - Ozhan Akyol; Aslinur Ozkaya-Parlakay; Eda Uluman; Belgin Gulhan; Tugba Bedir Demirdag; Selin Nar-Otgun (Taylor & Francis Group, 2020)
Meningococcal infections are an important cause of mortality and morbidity in childhood. Herein we report a 2-year-old Syrian refugee boy living in Turkey diagnosed with Neisseria meningitidis serotype B infection complicated with intracranial empyema. Refugees are a sensitive population in all aspects especially infectious diseases. Endemic diseases in the refugees' own countries constitute a major health problem. Vaccination in sensitive populations and in the country would be important precaution to decrease disease burden.